LEXICAL REPETITION OF A COHESIVE AND COHERENT TOOL IN AN ARTISTIC TEXT - Finiv, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In the key to the study of literary texts, it is important to highlight the role of the inner form of the word as the transponder of the explicit and implicit layers of the content of the literary text, the means of conceptualization (pregnancy) in the blocks of interpersonal communication. This is determined by the relevance of the chosen topic. Since most scholars emphasize the motivation of the IF word, in this work we will use the following definition: IF words – this is a motivational sign fixed in the word that is the bearer of imagery and contributes to the disclosure of the associative-figurative potential of the artistic text, the expression of intentions and communicative strategies and tactics in interpersonal communication. In our work, it is important to disclosure the role and functions of in-form nominations, repeated in the blocks of strategic tactical interaction of characters of flash fiction or in the author's speech. The material of the research makes it possible to draw the following discussion: repeated intraformal nominations used in the speech of characters of artistic texts of small prose are explicants of target-oriented communicative intentions, strategies and tactics, additional exponents of character characteristics, means of internal connectivity, and the internal form of such lexical units contributes to the expansion of the content boundaries of the text, the emergence of new associative-shaped shades, the actualization of new pragmatic meanings.